2021
DOI: 10.3389/fcimb.2021.720701
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Pattern of Extended Spectrum Beta Lactamase Producing Escherichia coli Isolated From Patients With Urinary Tract Infection in Morocco

Abstract: Extended-spectrum β-lactamases producing Escherichia coli (ESBL-EC) lend resistance to most β-lactam antibiotics. Because of limited treatment options, ESBL-EC infections are generally more difficult to treat, leading to higher hospital costs, reduced rates of microbiological and clinical responses, and a threat to the patient’s life. This study aimed to determine the antibiotic resistance pattern of ESBL-EC isolated from patients with urinary tract infection in Morocco. This retrospective laboratory-based stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
(76 reference statements)
4
13
0
Order By: Relevance
“…In comparison, ESBL-positive K. pneumoniae strains revealed similar resistance rates to cefotaxime (100%) and ceftazidime (85.4%). These data are consistent with previous studies conducted in China ( Quan et al., 2017 ), Nepal (Chander et al., 2013), Ethiopia ( Abayneh et al., 2018 ) and Morocco ( Kettani Halabi et al., 2021 ). In addition, cefoperazone/sulbactam, a third-generation cephamycin beta-lactamase inhibitor combination, had antibacterial potential against ESBL-producing isolates (resistance rates of 10.7% and 43.3% in E. coli and K. pneumoniae , respectively).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In comparison, ESBL-positive K. pneumoniae strains revealed similar resistance rates to cefotaxime (100%) and ceftazidime (85.4%). These data are consistent with previous studies conducted in China ( Quan et al., 2017 ), Nepal (Chander et al., 2013), Ethiopia ( Abayneh et al., 2018 ) and Morocco ( Kettani Halabi et al., 2021 ). In addition, cefoperazone/sulbactam, a third-generation cephamycin beta-lactamase inhibitor combination, had antibacterial potential against ESBL-producing isolates (resistance rates of 10.7% and 43.3% in E. coli and K. pneumoniae , respectively).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the prevalence of ESBL-producing isolates ( E. coli and K. pneumoniae ) was found more in males than females. The results are comparable to the studies done in Iran ( Peerayeh et al., 2016 ) and elsewhere ( Ouedraogo et al., 2016 ), but differ from other investigations that revealed that a high prevalence of ESBL producers detected in female patients ( Chander and Shrestha, 2013 ; Abayneh et al., 2018 ; Kettani Halabi et al, 2021 ). The reason for these differences is not clear.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations